Hybride und energieeffiziente Antriebe für mobile Arbeitsmaschinen 8. Fachtagung, 23. Februar 2021, Karlsruhe (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2021)
This book contains the collected conference proceedings to the lectures of the 8th symposium on 23rd February 2021 in Karlsruhe. The state of research and new developments in the field of drive technology for mobile machines are reported in 11 articles. The conference proceedings are characterised by technical contributions on intelligent machine control systems, innovative electrical drives and development methods for off-highway vehicles.